Characteristics of high‐ and low‐risk individuals in the PRIORITY study: urinary proteomics and mineralocorticoid receptor antagonism for prevention of diabetic nephropathy in Type 2 diabetes. Issue 10 (6th June 2018) - Tofte, N.; Lindhardt, M.; Adamova, K.; Beige, J.; Beulens, J. W. J.; Birkenfeld, A. L.; Currie, G.; Delles, C.; Dimos, I.; Francová, L.; Frimodt‐Møller, M.; Girman, P.; et al.
Abstract: Aim: To compare clinical baseline data in individuals with Type 2 diabetes and normoalbuminuria, who are at high or low risk of diabetic kidney disease based on the urinary proteomics classifier CKD273. Methods: We conducted a prospective, randomized, double‐blind, placebo‐controlled international multicentre clinical trial and observational study in participants with Type 2 diabetes and normoalbuminuria, stratified into high‐ or low‐risk groups based on CKD273 score. Clinical baseline data for the whole cohort and stratified by risk groups are reported. The associations between CKD273 and traditional risk factors for diabetic kidney disease were evaluated using univariate and logistic regression analysis. Results: A total of 1777 participants from 15 centres were included, with 12.3% of these having a high‐risk proteomic pattern. Participants in the high‐risk group ( n =218), were more likely to be men, were older, had longer diabetes duration, a lower estimated GFR and a higher urinary albumin:creatinine ratio than those in the low‐risk group ( n =1559, P <0.02). Numerical differences were small and univariate regression analyses showed weak associations ( R 2 < 0.04) of CKD273 with each baseline variable. In a logistic regression model including clinical variables known to be associated with diabetic kidney disease, estimated GFR, gender, log urinary albumin:creatinine ratio and use of renin‐angiotensin system‐blocking agents remained significant determinants of the CKD273 high‐risk group: area under the curve 0.72 (95% CI 0.68–0.75; P <0.01). Conclusions: In this population of individuals with Type 2 diabetes and normoalbuminuria, traditional diabetic kidney disease risk factors differed slightly between participants at high risk and those at low risk of diabetic kidney disease, based on CKD273. These data suggest that CKD273 may provide additional prognostic information over and above the variables routinely available in the clinic. Testing the added value will be subject to our ongoing study. (European Union Clinical Trials Register: EudraCT 2012‐000452‐34 and Clinicaltrials.gov: NCT02040441). What's new?: This paper describes baseline data from the first prospective multicentre study using the proteomics classifier CKD273 for risk stratification in individuals with normoalbuminuria and Type 2 diabetes. Previously, post hoc analyses have shown that CKD273 identifies individuals at high risk of developing diabetic kidney disease (DKD). The present study shows that the associations between the CKD273 proteomic pattern and traditional risk factors for DKD are weak, with small numerical differences for the traditional risk factors. CKD273 may provide additional information on risk of DKD. Interesting differences among sites across Europe in prevalence of CKD273 pattern cannot be explained by traditional risk factors for DKD.